Scintillation characteristics of heavily doped CsI:Tl, IO₃ crystals - Shpilinskaya, A.L.; Кudin, A.M.; Trefilova, L.N.; Zosim, D.J. (Вопросы атомной науки и техники, 2019)
The effect of IO⁻₃ ions on spectrometric characteristic of CsI:Tl crystal has been considered. It has been shown that co-doping of CsI:Tl crystal by IO⁻₃ anions permits to obtain clear ingots with increased thallium concentration up to CTl ~ 0.9 mole % in which the concentration quenching of photo- or radioluminescence do not observed. It has been shown that the decay of solid solution in CsI:Tl, IO₃ crystals is not observed, at least up to CTl ~ 0.5 mole %, as evidenced by a good energy resolution (R = 6.3%) of samples with the specified Tl concentration and this also evidenced by a larger segregation coefficient of thallium in CsI:Tl, IO₃ crystals (k = 0.24 contrary to k = 0.19 in CsI:Tl). An explanation of thallium solid solution stability in CsI matrix has been proposed which based on experimental fact of complex formation. Compensation of elastic stresses of opposite sign due to complex formation results in preventing of nucleation for solid solution decay. Розглянуто вплив аніонів IO⁻₃ на спектрометричні характеристики кристалів CsI:Tl. Показано, що легування кристалів CsI:Tl іонами IO⁻₃ дозволяє отримувати прозорі злитки зі збільшеною концентрацією талію (до CTl ~ 0,9%), котрі не мають ознак концентраційного гасіння фото- та радіолюмінесценції. Показано, що розпад твердого розчину в кристалах CsI:Tl, IO₃ не спостерігається, принаймні, до CTl ~ 0,5%, про що свідчать високий світловий вихід, гарне енергетичне розділення (R = 6,3%) зразків зі вказаною концентрацією і більший коефіцієнт розподілу талію в кристалах CsI:Tl, IO₃ (k = 0,24 проти k = 0,19 у CsI:Tl). Запропоновано пояснення більш високої стабільності твердого розчину в матриці CsI, яке базується на формуванні комплексів Tl+-IO⁻₃. Компенсація пружних напружень протилежного знаку внаслідок взаємодії катіонів і аніонів IO⁻₃ запобігає створенню зародків розпаду. Рассмотрено влияние анионов IO⁻₃ на спектрометрические характеристики кристаллов CsI:Tl. Показано, что легирование кристаллов CsI:Tl ионами IO⁻₃ позволяет получать прозрачные слитки с увеличенной концентрацией таллия (до CTl ~ 0,9%), которые не имеют признаков концентрационного тушения фото- и радиолюминесценции. Показано, что распад твердого раствора в кристаллах CsI:Tl, IO₃ не наблюдается, по крайней мере, до CTl ~ 0,5%, о чем свидетельствуют высокий световой выход, хорошее энергетическое разрешение (R = 6,3%) образцов с указанной концентрацией и больший коэффициент распределения таллия в кристаллах CsI:Tl, IO₃ (k = 0,24 против k = 0,19 в CsI:Tl). Предложено объяснение более высокой стабильности твердого раствора таллия в матрице CsI, которое основано на образовании комплексов Tl+-IO⁻₃. Компенсация упругих напряжений противоположного знака вследствие взаимодействия катионов и анионов IO⁻₃ предотвращает образование очагов распада.